Non-linear Effects of Fiscal Policy in Germany: A Markov-Switching Approach - Florian Höppner; Katrin Wesche (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
Keynesian theory suggests that a reduction in government expenditure has a negative effect on private demand and therefore on output. Contrary, neoclassical theory argues that reduced public expenditure makes room for an expansion of the private sector and thus has a stimulating effect on the economy. Additionally, expectations of a lower tax burden in the future should stimulate consumption. The recent literature discusses that both theories might be right at different times. Especially, during times of fiscal contractions from high levels of debt the economy might react in a neoclassical way. In this paper, we test for non-linear effects of fiscal policy in a Markov-switching approach. We find two different regimes, with a neoclassical regime prevailing around 1972-74, 1979-82 and 1991-93. Furthermore, using time-varying transition probabilities (TVTP) for the Markov process, we test if the neoclassical reaction of private consumption to fiscal variables depends on some!
Keywords: E62; E21; C22; 330; fiscal policy; private consumption; Markov-switching; time-varying transition probabilities